Interprofessional collaboration: three best practice models of interprofessional education - Bridges, Diane R. (Medical Education Online, 2011)
Interprofessional education is a collaborative approach to develop healthcare students as future interprofessional team members and a recommendation suggested by the Institute of Medicine. Complex medical issues can be best addressed by interprofessional teams. Training future healthcare providers to work in such teams will help facilitate this model resulting in improved healthcare outcomes for patients. In this paper, three universities, the Rosalind Franklin University of Medicine and Science, the University of Florida and the University of Washington describe their training curricula models of collaborative and interprofessional education. The models represent a didactic program, a community-based experience and an interprofessional-simulation experience. The didactic program emphasizes interprofessional team building skills, knowledge of professions, patient centered care, service learning, the impact of culture on healthcare delivery and an interprofessional clinical component. The community-based experience demonstrates how interprofessional collaborations provide service to patients and how the environment and availability of resources impact one's health status. The interprofessional-simulation experience describes clinical team skills training in both formative and summative simulations used to develop skills in communication and leadership. One common theme leading to a successful experience among these three interprofessional models included helping students to understand their own professional identity while gaining an understanding of other professional's roles on the health care team. Commitment from departments and colleges, diverse calendar agreements, curricular mapping, mentor and faculty training, a sense of community, adequate physical space, technology, and community relationships were all identified as critical resources for a successful program. Summary recommendations for best practices included the need for administrative support, interprofessional programmatic infrastructure, committed faculty, and the recognition of student participation as key components to success for anyone developing an IPE centered program.